2013
DOI: 10.1155/2013/438384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sorbent Characteristics on Fouling and Deposition in Circulating Fluid Bed Boilers Firing High Sulfur Indian Lignite

Abstract: 125 MWe circulating fluidized bed combustion (CFBC) boiler experienced severe fouling in backpass of the boiler leading to obstruction of gas flow passage, while using high sulfur lignite with sorbent, calcium carbonate, to capture sulfur dioxide. Optical microscopy of the hard deposits showed mainly anhydrite (CaSO4) and absence of intermediate phases such as calcium oxide or presence of sulfate rims on decarbonated limestone. It is hypothesized that loose unreacted calcium oxides that settle on tubes are sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Hence, these elements played an important role in the initial stages of ash deposition. , The viscosity of fine ash was significantly affected by the addition of limestone as a sorbent owing to changes in its chemical composition, which also changed its deposition behavior. Limestone addition also likely changed the structure of ash deposits, since CaO particles deposited on the surface of the probe reacted with CO 2 or SO 2 , resulting in the formation of bonded ash deposits. , Based on the above analysis, ash DP showed nonlinear variation as a function of the Ca/S ratio, affecting both the formation of fly ash and ash deposits.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, these elements played an important role in the initial stages of ash deposition. , The viscosity of fine ash was significantly affected by the addition of limestone as a sorbent owing to changes in its chemical composition, which also changed its deposition behavior. Limestone addition also likely changed the structure of ash deposits, since CaO particles deposited on the surface of the probe reacted with CO 2 or SO 2 , resulting in the formation of bonded ash deposits. , Based on the above analysis, ash DP showed nonlinear variation as a function of the Ca/S ratio, affecting both the formation of fly ash and ash deposits.…”
Section: Resultsmentioning
confidence: 97%
“…However, taking the process of ash deposition into consideration, the conditions influencing carbonation reactions are likely to be more complicated. Under air-firing conditions, with about 15% CO 2 in flue gas, agglomeration and fouling of heating surfaces occur owing to carbonation and sulfation. Previous research results also indicated that the ash deposition rate largely depended on the content of free CaO in the fly ash . Under oxy-fuel firing, with up to 85% CO 2 in the flue gas, potential problems related to carbonation reactions are yet to be evaluated, although there is evidence for concern.…”
Section: Introductionmentioning
confidence: 99%
“…2) Recently, not only the wastes are incinerated, but also diversified efforts to recover the energy produced after combustion are being continued, and diversified studies are in progress to investigate the cause for generation of ash deposits recognized as the major factor for degradation in the boiler efficiency as well as to reduce their generation. [3][4][5] Since not only deposition of fine particles produced in combustion process but also chemical reaction and condensation of diversified components act in a combined way for generation of the ash deposits, the generation mechanism is known to be very complicated. 6) The ash deposits are formed by a combined action of physical and chemical phenomena.…”
Section: Introductionmentioning
confidence: 99%